2017
DOI: 10.1371/journal.pone.0188361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term irrigation patterns on phosphorus forms and distribution in the brown soil zone

Abstract: Continuous application of P fertilizers under different irrigation patterns can change soil phosphorus (P) chemical behavior and increase soil P levels that are of environmental concern. To assess the effect of long-term different irrigation patterns on soil P fractions and availability, this study examined sequential changes in soil organic P and inorganic P from furrow irrigation (FI), surface drip irrigation (SUR), and subsurface drip irrigation (SDI) in the brown soil zone (0–60 cm) during 1998 to 2011. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The concentrations of phosphorus in the effluent are usually about 10 mgL -1 , which is beneficial to plant development ( Hanjra et al, 2012 ). In contrast, its continuous application for irrigation can change soil phosphorous behavior and become another environmental concern from agricultural runoff ( Liu et al, 2017 ). Additionally, phosphorus can cause eutrophication or toxicity in other habitats ( Jaramillo and Restrepo, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of phosphorus in the effluent are usually about 10 mgL -1 , which is beneficial to plant development ( Hanjra et al, 2012 ). In contrast, its continuous application for irrigation can change soil phosphorous behavior and become another environmental concern from agricultural runoff ( Liu et al, 2017 ). Additionally, phosphorus can cause eutrophication or toxicity in other habitats ( Jaramillo and Restrepo, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Frequent application of fertilizer P during the year-round production and the availability of cations to bind it as insoluble fraction may have facilitated the higher build up of TP in the areas with longer histories of irrigation in both the schemes. Liu et al (2017), found out that among all forms of irrigation they evaluated, furrow irrigation led to the greatest accumulation of TP at topsoil layer.…”
Section: Variability Of Different Forms Of P and K With Periods Of Irmentioning
confidence: 95%
“…From the figure, however, it could be discerned that the predominance of higher concentrations is at non-irrigated area and at areas with fewer years of irrigation. Addition of large volume of water to the soil as is the practice in both the schemes may favour accumulation TP as postulated by Liu et al (2017). According to them long term irrigation may harden the soil and restrict the mobilization and transport of P into soil profiles.…”
Section: Spatial Distribution Of P and K Forms In Different Periods Omentioning
confidence: 97%
See 1 more Smart Citation
“…Drip irrigation is an effective technology for increasing P availability [18]. However, phosphorus fertilizer contains HPO 4 2− that would react with Ca 2+ and Mg 2+ , which can form the insoluble CaHPO 4 or MgHPO 4 precipitates and lead to drip irrigation clogging [53,54].…”
Section: Phosphate Fertilizermentioning
confidence: 99%